A Study of Chronic Disease Management in Indonesian Primary Health Care - Febri Endra Budi Setyawan; Retno Lestari (Indian Journal of Forensic Medicine & Toxicology, 2022)
Chronic disease management program in Indonesia(Prolanis) is a preventive and promotive programdeveloped by Indonesian national health insurance. The initial survey showed thatonly 37.04% ofprimary health careperformchronic disease management programsoptimally. Prolanis can succeed andbe sustained if health care services included health care teams effectively address patient needs as wellas increasing the quality of health services.For this reason, physicians as key roles in primary health careshould enhance their competencies to deliver high-quality care. This study aimed to identify the impactof physician competencies on patient satisfaction in Indonesian primary health care. This study useda cross-sectional designwith multistage random sampling which included 90 chronic disease patientsin primary health care. The results revealed that the average physician competencies in providinghealth services to patients were 73.57%. In addition to this, as many as 73.64% of patients expressedsatisfaction with physician skills. Lambda correlation test obtained a value of r = 0.76, so it was statedthat the physician competencies had a strong influence on chronic disease patient satisfaction. It canbe concluded that the more physicians master their competencies,the more confident patients seektreatment at primaryhealth care.